DEVELOPMENT OF THE ARIS MODULE (ANXIETY AND DEPRESSION REDUCTION THROUGH ISLAMIC SPIRITUAL CARE) FOR CHRONIC ILLNESS NURSING PRACTICE - Aris Citra Wisuda; Citra Suraya; Tukimin bin Sansuwito; Atma Deviliawati; Santi Rosalina; Heriziana Hz; Yofa Anggriani Utama (Journal Of Nursing Science Research, 2025)
Anxiety and depression are common psychological problems experienced by patients with chronic illnesses, potentially worsening their clinical condition and quality of life. Nursing interventions that integrate an Islamic spiritual approach are considered to have the potential to enhance psychological calmness when coping with long-term disease. This study aimed to develop and assess the effectiveness of the ARIS Module (Anxiety and Depression Reduction through Islamic Spiritual Care) as a nursing intervention guideline to address anxiety and depression among patients with chronic illnesses. The study employed a Research and Development (R&D) design using the ADDIE model, which includes needs analysis, design, content development, implementation in nursing practice, and evaluation. Effectiveness testing was conducted through a quasi-experimental pretest–posttest design involving 140 chronic illness patients who received care from January 2025 to July 2025 at Siti Khadijah Islamic Hospital Palembang. The Hamilton Anxiety Rating Scale (HARS) and the Beck Depression Inventory-II (BDI-II) were used as measurement instruments. The findings revealed that the implementation of the ARIS Module significantly reduced anxiety and depression levels (p < 0.05) compared to pre-intervention scores. Patients also reported improved spiritual comfort and emotional support from nurses. This module was considered feasible, practical, and relevant for use in nursing practice focused on holistic care. The study recommends broader implementation of the module across various nursing services and the development of training programs to enhance nurses’ competencies in spiritual care.